Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Assume $f(x)>0$ defined in $[a,b]$,and for a certain $L>0$,$f(x)$ satisfies the Lipschitz condition$|f(x_1)-f(x_2)|\leq L|x_1-x_2|$.

Assume that for $a\leq c\leq d\leq b$,$$\int_c^d \frac{1}{f(x)}dx=\alpha,\int_a^b\frac{1}{f(x)}dx=\beta$$Try to prove$$\int_a^b f(x)dx \leq \frac{e^{2L\beta}-1}{2L\alpha}\int_c^d f(x)dx$$

share|improve this question
1  
Is this homework? It's stated as if it were something akin to it. –  cardinal Apr 29 '12 at 3:25

2 Answers 2

up vote 2 down vote accepted
+25

I got something which is rather close to your result but couldn't get rid of an additional term. I'm hoping someone will find the development useful in order to give a complete answer. The question reminded me somehow of the proof of Gronwall's inequality and my answer is based on that.

Let $h(t)=\int_a^t f(s)ds$ taking the derivative with respect to $t$ yields $h'(t) = f(t)$. Rewriting $f(t)=f^2(t)/f(t)$, we can find an upper bound for $f^2(t)$ indeed, we have: $$f^2(t) = \int_a^t (f^2(s))'ds + f^2(a) = 2\int_a^t f(s)f'(s)ds +f^2(a)$$

but then, the Lipschitz continuity implies that $|f'(s)|\le L$ which yields

$$f^2(t) \le 2L \int_a^t f(s)ds + f^2(a)\quad \Longrightarrow \quad h'(t) \le \left(2Lh(t) +f^2(a)\right)\left({1\over f(t)}\right) $$ we can then introduce the additional positive term $\left(\int_c^df(t)dt\right)/\alpha$ with: $$ h'(t) \le \left(2L h(t)+f^2(a) + {\int_c^d f(s)ds\over \alpha}\right)\left({1\over f(t)}\right) $$ Remark: the additional term comes from the $f^2(a)$. We could get rid of it if $\left(\int_c^d f(s)ds\right)/\alpha > f^2(a)$ which I wasn't able to prove.

To simplify notations, let $a=f^2(a) + {\int_c^d f(s)ds\over \alpha},$ $b=2L$ and $g(t)=1/f(t)$ then. Then the previous inequality reads $$h'(t) \le g(t)(a+bh(t))$$ which can be rewritten as follows (here is where it starts to look like Gronwall's inequality):

$$ {(a+bh(t))'\over a+bh(t)} \le bg(t) $$

the left-hand side is the logarithmic derivative of $a+bh(t)$, integrating both sides from $a$ to $t$ yields

$$ a+bh(t) \le a\exp\left(b\int_a^t g(t) \right) $$

plugging the values of $a$,$b$ and using $\int_a^b g(t) = \beta$, we finally get:

$$\int_a^b f(s)ds = h(b) \le \color{green}{\left[{\exp(2L\beta)-1\over 2L\alpha}\right]\int_c^d f(s)ds} + \color{red}{{f^2(a)\over 2L}\left(\exp(2L\beta)-1\right)} $$

share|improve this answer
    
1.h′(t)=f(t).2.The main problem is that I don't assume that f is derivable.So you may have to improve your method.Thanks. –  Joe Apr 30 '12 at 0:39
    
Yes but I believe that the Lipschitz continuity of $f$ implies that $f$ is differentiable almost everywhere (I believe that this is called Lebesgue's theorem) and that $$\left(f(b)-f(a)\right)=\int_a^b f'(t)dt$$ I agree however that the development can certainly be made more rigorous but the idea was rather to suggest a possible method. –  tibL Apr 30 '12 at 7:26
    
Since it is a bounty question,I hope that you can show me a rigorous proof. Thanks. Anyway, I appreciate your help. –  Joe Apr 30 '12 at 10:09

If $f(x)$ is smooth, or $f\in C^1$, assume $\displaystyle h(t)=\int_a^t f(s)\mathrm{d}s$, and $\displaystyle g(t)=\int_a^{t}\frac{1}{f(s)}\mathrm{d}s$,we just can focus on \begin{equation} \frac{h(t)}{\exp(2Lg(t)-1)} \end{equation}

because we know that there is a $\xi\in(c,d)$ s.t. \begin{equation} \frac{h(d)-h(c)}{g(d)-g(c)}=\frac{h'(\xi)}{g'(\xi)}=f^2(\xi) \end{equation}

thus we just prove $$\frac{h(t)}{\exp(2Lg(t)-1)}\le\frac{\min_{[a,b]}f^2(\xi)}{2L}$$

To find the minimum. Let's compute the derivative and we also can see the LHS function at $t=a$ has a limit as $f^2(a)/2L$.

Assume the LHS term is $\gamma(t)$, then \begin{equation} \gamma'(t)=\frac{h'(\exp(2Lg)-1)-2Lg'\exp(2Lg)h}{(\exp(2Lg)-1)^2} \end{equation}

It is easy to compute the limit at $t=a$, we find that $\gamma'(a)=\frac{f(a)f'(a)}{2L}-\frac{1}{2}f(a)\le0$. And we shall see that if we set \begin{eqnarray} p(t)&=&f\cdot(h'(\exp(2Lg)-1)-2Lg'\exp(2Lg)h)\\ &=&f^2(\exp(2Lg)-1)-2L\exp(2Lg)h \end{eqnarray}

We can see that $p(a)=0$, since $h(a)=0$ and $g(a)=0$. However, \begin{eqnarray} p'(t)&=&2ff'(\exp(2Lg)-1)-4L^2\exp(2Lg)h/f\\ &\le&\frac{2L}{f}(f^2(\exp(2Lg)-1)-2L\exp(2Lg)h)\\ &=&\frac{2L}{f}p(t) \end{eqnarray}

Thus we shall know that $p(t)\le 0$, since $\{(\exp(-2Lg(t))p\}'\le0$,and $p(a)=0$.

So we shall get that $\gamma'(t)\le 0$.

Thus $\gamma$ is decreasing in $t$, $\gamma(t)\le\gamma(a)$.

On the other hand. Take $\displaystyle\int_{t}^b f(s)\mathrm{d}s=\phi(t)$,$\displaystyle\int_{t}^b\frac{1}{f(s)}\mathrm{d}s=\psi(t)$.

Then we also can see that \begin{equation} \beta(t)=\frac{\phi(t)}{\exp(2L\psi(t)-1)} \end{equation} which has $\displaystyle\beta(b)=\frac{f^2(b)}{2L}.$

with the same process(PAY ATTENTION TO THE SIGN), $$\beta'(b)=\frac{f(b)f'(b)}{2L}+\frac{f(b)}{2}\ge 0.$$

And also we can obtain that $$q(t)=2L \exp(2L \psi)\phi-f^2(\exp(2L\psi)-1)\ge 0$$

which means $\beta(t)$ is increasing in $t$, which is $\beta(t)\le\beta(b)$.

Since $\beta(a)=\gamma(b)$, thus $\gamma(b)\le \min(f^2(a),f^2(b))/2L$.

AND the choice of $b$ is arbitrary, we know that for any $t$, we have $$\gamma(t)\le f^2(t)/2L$$

Consider the $\min_{[a,b]}f^2(t)$ is reached at $t=\upsilon$, then $\gamma(\upsilon)\le f^2(\upsilon)/2L$, since $\gamma(t)$ is decreasing in $t$. Thus $\gamma(b)\le f^2(\upsilon)/2L$. $\Box$

share|improve this answer
    
When $f$ is Lip. I think one can apply convolution to it to make it smooth. And we can approximate both sides. –  Yimin May 3 '12 at 21:57
    
1. I don't understand how you obtain the inequality $\gamma(t) \leq \frac{f(t)^2}{2L}$ "since the choice of $b$ is arbitrary". When $t$ varies, $\gamma(a)$ stays $\gamma(a)$. –  Ewan Delanoy May 4 '12 at 5:13
    
2. How do you obtain $\gamma(b) \leq \frac{f(v)^2}{2L}$ from $\gamma(v) \leq \frac{f(v)^2}{2L}$ ? You can't just replace $\gamma(v)$ with $\gamma(b)$. –  Ewan Delanoy May 4 '12 at 5:15
    
for your last question, since $\gamma$ is decreasing. I proved one thing the integral. If you consider $a$ and $b$ are both variables, then $\gamma(a,b,t)\le\min(\gamma(a,b,a),\gamma(a,b,b))$ –  Yimin May 4 '12 at 17:13
    
You shall see the definition of $\gamma$, it is $h(t)/\exp(2Lg(t)-1)$, in which, $h$ and $g$ are integrals from $a$ to $t$. thus if for $b\ge a$, we have $h(t)/\exp(2Lg(t))-1)\le f^2(b)/2L$,for any $t\in[a,b]$, we should have the same thing if we consider $b$ as a variable. –  Yimin May 4 '12 at 17:18

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.